The multi-ethnic family connections of Rosa Clay, the first Finn of African descent, in late nineteenth-century South West Africa - Merivirta, Raita (Informa UK Limited, 2026)
This article takes a biographical approach to examine the story of Rosa Emilia Clay (1875–1959), later Lemberg, the first Finn of African descent, and Afro-European transnational and transcultural relations in Omaruru, South West Africa, in the 1870s and 1880s. In this article, the beginnings of Rosa’s ‘global life’, her biological parents and the placing of Rosa with a Finnish missionary couple are examined with the help of archival research, digitised newspapers and periodicals and some detective work online, especially exploration of genealogical websites and digitised census data, as well as baptism, marriage and death records.